A case study analysis of a high performance environment in elite swimming - Fletcher, D.; Streeter, A. (Journal of change management, 2016)
Previous performance environment research in sport has either focused on specific variables in relative isolation or a multitude of variables without theoretically linking them together. Using a case study approach, we explored the high performance environment (HPE) in an elite swimming team through the theoretical lens of the HPE model [Jones, J. G., Gittins, M. J., & Hardy, L. (2009). Creating an environment where high performance is inevitable and sustainable: The high performance environment model. Annual Review of High Performance Coaching and Consulting, 1, 139-149]. The HPE model consists of four core components and a number of subcomponents: leadership (vision, support, challenge), performance enablers (information, instruments, incentives), people (attitudes, behaviours, capacity), and organizational culture (achievement, well-being, innovation, internal processes). The findings illustrate the relationships between a wide range of factors and sport performance, and provide qualitative evidence for the HPE model in an elite sport context. Nevertheless, several revisions are suggested in terms of integrating additional relevant concepts and considering differential weighting of the model's components. For practitioners operating in elite sport, adopting a holistic view of the performance environment draws attention to the numerous organizational influences on sport performers and encourages a more coordinated approach to developing high performance. Practitioners attempting to effectively intervene at an environmental level will need to be able to coach leaders, facilitate performance enablers, engage people, and shape cultural change.